Interconnectivity of the Vardar and Struma river valleys. Some hints to the understanding of the south-eastern Balkans role in the 2nd millennium BC - Bahyrycz, Cezary (Folia Praehistorica Posnaniensia, 2022)
The Vardar and Struma rivers flow through the south-eastern Balkans, creating valleys which have been inhabited by human populations for thousands of years. From an archaeological perspective, from Neolithic times these corridors have long been considered crucial for establishing cultural, trade, and social networks, developed later by the emergence of cultural complexes of Late Bronze Age. This area was incorporated into wide archaeological frameworks of interregional interaction, namely – the world-system theory and its variants. The aim of this paper is an attempt to apply these theoretical models as well as concept of “contact space” to human interactions in the Vardar and Struma rivers’ valleys in the 2nd millennium BC. It analysis bases on tableware pottery evidences with data concerning presence of defensive outposts within easy to control mountainous paths, as well as chosen information deriving from funeral rites. These data may provide insights into the communication networks in south-eastern Balkans and mentioned river valleys may seem as an important area of mutual influences.